2022
DOI: 10.15585/mmwr.mm7108e2
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Emergency Department Visits Associated with Mental Health Conditions Before and During the COVID-19 Pandemic — United States, January 2019–January 2022

Abstract: On February 18, 2022, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).In 2021, a national emergency* for children's mental health was declared by several pediatric health organizations, and the U.S. Surgeon General released an advisory † on mental health among youths. These actions resulted from ongoing concerns about children's mental health in the United States, which was exacerbated by the COVID-19 pandemic (1,2). During March-October 2020, among all emergency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(106 citation statements)
references
References 10 publications
6
100
0
Order By: Relevance
“…These results coincide with those obtained in Australia and the US. (13,25) In fact, an increase in MHR ED utilization among adolescent girls aged 12-17 years was also seen in New South Wales during the first year of the pandemic (January 2020 to February 2021). ( 13) Weekly ED visits for adolescent girls also increased for eating and tic disorders in 2020-2021 and depression and obsessive-compulsive disorder in 2021 compared to 2019 in the US.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results coincide with those obtained in Australia and the US. (13,25) In fact, an increase in MHR ED utilization among adolescent girls aged 12-17 years was also seen in New South Wales during the first year of the pandemic (January 2020 to February 2021). ( 13) Weekly ED visits for adolescent girls also increased for eating and tic disorders in 2020-2021 and depression and obsessive-compulsive disorder in 2021 compared to 2019 in the US.…”
Section: Discussionmentioning
confidence: 99%
“…While both MHR and overall ED visits first decreased during 2020, (7-12, 14-17, 21-24) some studies have reported increased MHR ED utilization during 2021 and early 2022. (13,25) During this time, overall pediatric ED utilization has remained lower than pre-COVID-19 levels. (6,25) So far, the bulk of the evidence regarding changes in pediatric MHR ED utilization has originated from the United States, thereby limiting the generalisability of findings to other countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We assessed trends in the number of alcohol-related ED visits among people aged ≥15 years and weekly alcohol-related ED visit rates (per 10,000 ED visits) overall, by population characteristics, and by quarter (Q) during 2020 compared with corresponding quarters during 2018–2019. Because of fluctuations in facilities reporting to the NSSP over time, data were included from the facilities that were consistently reporting throughout the study period so that only facilities with more complete data were included ( Radhakrishnan et al, 2022 ) (where the facility-level average percentages for reporting diagnosis codes to the NSSP was ≥70%). Analyses focused on rates per 10,000 ED visits because of the substantial decline in total ED visits during the onset of the COVID-19 pandemic ( Adjemian et al, 2021 ; Hartnett et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%